Peran kelompok tani terhadap usahatani padi di Kecamatan Sale Kabupaten Rembang - Fitra Margi Nugroho; Sriroso Satmoko; Karno Karno (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
Farming development through farmer groups is an effort to accelerate the improvement of farmers' welfare. The purpose of this research was to analyze the role of farmer groups as learning class, cooperation vehicle, and production unit in influencing farmer behavior, access of production facilities, application of Integrated Crop Management (ICM) and farming profit. The research population was members of farmer groups in Kecamatan Sale Kabupaten Rembang who have irrigated land with an area of 0.2-0.5 Ha. Determination of sampling was done by using purposive random sampling method with total sample of 276 farmers. Interviews with questionnaires were used as data collection methods. Data were analyzed using path analysis to know the relationships between variables. Results of research indicated that role of farmer group as study class, cooperation vehicle, and production unit had an effect to farmer behavior. The role of farmer groups as a vehicle for cooperation, production unit and farmer behavior had an effect on access production facilities. Behavior of farmers and access to production facilities affected the application of ICM. The application of ICM had an effect on the profit of farming. R/C Ratio of paddy farming in Sale District, Rembang Regency was equal to 1,23. Keywords : farmer group; farmer behavior; application of ICM